Redox Homeostasis in Cardiovascular Disease: The Role of Mitochondrial Sirtuins - Zullo, Alberto; Guida, Rosa; Sciarrillo, Rosaria; Mancini, Francesco P. (Frontiers in Endocrinology, 2022)
Cardiovascular disease (CVD) is still the leading cause of death worldwide. Despite successful advances in both pharmacological and lifestyle strategies to fight well-established risk factors, the burden of CVD is still increasing. Therefore, it is necessary to further deepen our knowledge of the pathogenesis of the disease for developing novel therapies to limit even more its related morbidity and mortality. Oxidative stress has been identified as a common trait of several manifestations of CVD and could be a promising target for innovative treatments. Mitochondria are a major source of oxidative stress and sirtuins are a family of enzymes that generate different post-translational protein modifications, thus regulating important cellular processes, including cell cycle, autophagy, gene expression, and others. In particular, three sirtuins, SIRT3, SIRT4, and SIRT5 are located within the mitochondrial matrix where they regulate energy production and antioxidant pathways. Therefore, these sirtuins are strongly involved in the balance between oxidant and antioxidant mechanisms. In this review, we summarize the activities of these sirtuins with a special focus on their role in the control of oxidative stress, in relation to energy metabolism, atherosclerosis, and CVD.